Power System Protective Relaying. - Das, J. C. (CRC Press, 2017)
"This book focuses on protective relaying, which is an indispensable part of electrical power systems. The recent advancements in protective relaying are being dictated by MMPRs (Microprocessor based multi-function relays). The text covers smart grids, integration of wind and solar generation, microgrids, and MMPRs (Microprocessor based multi-function relays) as the driving aspects of innovations in protective relaying. Topics such as cyber security and instrument transformers are also explored. Many case studies and practical examples are included to emphasize real-world applications."--Provided by publisher